Antagonistic Interactions Between Fusaria Species and Their Host Plants Are Influenced by Host Taxonomic Distance: A Case Study From Mexico - Benítez-Malvido, Julieta; Rodríguez-Alvarado, Gerardo; Álvarez-Añorve, Mariana; Ávila-Cabadilla, Luis D.; del-Val, Ek; Lira-Noriega, Andrés; Gregorio-Cipriano, Rosario (Frontiers in Ecology and Evolution, 2021)
Interactions between cultivated and wild plants with their fungal pathogens have strong ecological, evolutionary and economic implications. Antagonistic interactions, however, have been scantily studied in an applied context by using ecological networks, phylogeny and spatial ecology concurrently. In this study, we describe for the first time, the topological structure of plant-fungi networks involving species of the genus Fusarium and their native and introduced (exotic) cultivated host plants in Mexico. For this, we based our study on a recent database describing the attack on 75 native and introduced plant species, including 35 species of the genus Fusarium. Host plant species varied in their degree of phylogenetical relatedness (Monocots and Dicots) and spatial geographical distribution. Therefore, we also tested whether or not plant-Fusarium networks are phylogenetically structured and highlighted the spatial correlation between pathogens and their host plants across the country. In general, the pathogen-plant network is more specialized and compartmentalized in closely related taxa. Closely related hosts are more likely to share the same pathogenic Fusarium species. Host plants are present in different ecosystems and climates, with regions having more cultivated plant species presenting the highest number of fusaria pathogens. From an economic standpoint, different species of the same taxonomic family may be more susceptible to being attacked by the same species of Fusarium, whereas from an ecological standpoint the accidental movement of pathogens with their host plants may expose wild and cultivated plants to new diseases. Our study highlights the relevance of interaction intimacy in structuring trophic relationships between plants and fusaria species in native and introduced species. Furthermore, we show that the analytical tools regarding host distribution and phylogeny could permit a rapid assessment of which plant species in a region are most likely to be attacked by a given fusaria.